Agraryzm w teorii i praktyce - Romanow, Zbigniew (Wydział Prawa i Administracji UAM, 1990)
Agrarism, as a socio-economic doctrine, develops in countries with a prevailing agricultural sector, especially in years 1918 - 1939. The changes connected with land reforms and the transition of European agriculture into capitalism deepened the disproportions between towns and countryside. Therefore, among the activists of agrarian movements in agricultural countries appeared the view stressing the necessity of socio-economic changes leading to the elevation of the significance of agriculture in the nation's life. The beginnings of agrarism on Polish territory appeared early in the XXc. Taking as an example agricultural relations in Denmark and Czechoslovakia, Polish agrarians put forth the postulate of subordinating the policy of the State to the overall development of farms. An attachement to the principles of market economy and a so-called right of deconcentration made agrarians consider agriculture to be the basic branch of national economy. In turn, they were usually against the development of industry not connected with agriculture. Their postulates included the restriction of big land ownership and the parcellation of land among peasants capable of efficient farming based on family labour resources. The agrarian movement, prosecuted during the four decades of „socialist construction" in Poland, has not enirely lost its significance. Some deformations of views from that period are presently corrected under changed political, social and economic conditions. The replacement of the directival-distributive system with the market system in difficult conditions of demand imbalance makes it necessary to exert the economic pressure with respect to the economy as a whole. The point is to stipulate the growth of the most efficient sectors of economy. The adoption of the principles of free competition accompanied by simultaneous demands for a preferential treatment of agriculture together with a far-reaching interventionist policy of the State is determined by the present character of the market-place and the direction of changes. State interventionism is to correct, not to replace, the market mechanism. A precondition for efficient regulation of economic processes is the creation of market economy. State interventionism must not be a mere social aid for all farmers. It should aim at securing the profitability of agricultural activity only for efficient farms.
Agrarism in theory and practice